2005
DOI: 10.1159/000084161
|View full text |Cite
|
Sign up to set email alerts
|

How Many Cravings? Pharmacological Aspects of Craving Treatment in Alcohol Addiction: A Review

Abstract: In the last decade, craving has increasingly been considered an important target for the treatment of patients with alcohol problems, and several drugs able to interfere with the neurotransmitters involved in craving mechanisms have been experimented. However, different subtypes of patients could have different mechanisms at the basis of alcohol craving. In this review, the main drugs currently used in the treatment of patients with alcohol problems are described. A hypothesis of pharmacological treatment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 135 publications
0
45
0
10
Order By: Relevance
“…For this hypothesis to be tested, an evaluation instrument will need to be developed (Redish et al, 2008). Another matching example is provided by Addolorato et al Based on the three types of craving proposed by Verheul et al (1999), Addolorato et al (2005) proposed naltrexone and GHB (gamma-hydroxybutyric acid) for reward craving; acamprosate, GHB, and baclofen for relief craving; and selective serotonin reuptake inhibitors (SSRI), baclofen, topiramate, and odansetron for obsessive craving. Research by Ooteman et al revealed different mechanisms of action for anticraving medications.…”
Section: Discussionmentioning
confidence: 99%
“…For this hypothesis to be tested, an evaluation instrument will need to be developed (Redish et al, 2008). Another matching example is provided by Addolorato et al Based on the three types of craving proposed by Verheul et al (1999), Addolorato et al (2005) proposed naltrexone and GHB (gamma-hydroxybutyric acid) for reward craving; acamprosate, GHB, and baclofen for relief craving; and selective serotonin reuptake inhibitors (SSRI), baclofen, topiramate, and odansetron for obsessive craving. Research by Ooteman et al revealed different mechanisms of action for anticraving medications.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were strongly advised against using drugs that could potentially influence craving for alcohol. 31,32 Blood alcohol tests and urinalysis were performed 12 times (twice per week, for 6 weeks) for those patients concluding the study procedures.…”
Section: Procedures and Assessmentsmentioning
confidence: 99%
“…As the issue of the clinically heterogeneous nature of the addiction was attempted to be solved during the last fifty years, various sub-classifications of patients were suggested. Such a division into subtypes has the purpose to assist in determination of targeted therapy when predicting the disease prognosis 35,44,45 . Clinical studies confirmed that classifying patients into more homogeneous groups would enable setting not only the most effective psychopharmacotherapy but appropriate psychotherapy treatment as well 46 .…”
Section: Subtypes Of Alcoholismmentioning
confidence: 99%